INSTABILITY PROBLEM OF CONVENTIONAL TRANSFORMER DIFFERENTIAL PROTECTION-APPLICATION OF ZERO SEQUENCE CURRENT TRAP - O A., Ezechukwu (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
Zero sequence component of current usually causes instability of the differential protection. It enters circuits through earthed terminals. The traditional way of solving the problem in differential schemes is by connecting the interposing current transformers (ICTs) in delta since there is no path for zero sequence component of current in delta. This paper suggests another way of dealing with the problem. A zero sequence trap is modeled to pass the zero sequence current through an output logic which ensures that operation of the relay is enabled only when there is a real differential fault.